2013
DOI: 10.1111/sed.12045
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic controls of spatial and temporal variations in modern fluvial tufa sedimentation: A thirteen‐year record from a semi‐arid environment

Abstract: Sedimentological and hydrochemical parameters of the River Piedra (northeast Spain) were monitored every six months (from 1999 to 2012) at 24 sites, at which tablets were installed all along the river. The river water is of HCO 3 -SO 4 -Ca type and is notably influenced by inputs from upstream karstic springs. Tufa deposition was first detected 8 km downstream of these springs and greatly increased from there, primarily along the steeper stretch (i.e. within the Monasterio de Piedra Natural Park); then, deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 56 publications
4
99
0
Order By: Relevance
“…Gradzinski et al, 2014), wedge-shaped valley fill travertines (e.g. Arenas et al, 2014;Huerta et al, 2016) and a mixed travertine-terrigenous system (Croci et al, 2016) have been reported. The overall geobody of the Budakalász travertines was described as a mound/fissure ridge complex (Scheuer and Schweitzer, 1985;Pentecost, 2005).…”
Section: Geobody Architecture and Lithofaciesmentioning
confidence: 99%
“…Gradzinski et al, 2014), wedge-shaped valley fill travertines (e.g. Arenas et al, 2014;Huerta et al, 2016) and a mixed travertine-terrigenous system (Croci et al, 2016) have been reported. The overall geobody of the Budakalász travertines was described as a mound/fissure ridge complex (Scheuer and Schweitzer, 1985;Pentecost, 2005).…”
Section: Geobody Architecture and Lithofaciesmentioning
confidence: 99%
“…S PL and S PS 2 are located on the stream bed below the Panda Waterfall and in a depression on the Pearl Shoal with turbulent flow, respectively. High flow velocities and turbulence enhance CO 2 , which favors CaCO 3 precipitation at S PS 2 and S PL [6,15,34], and when the water velocity is greater than 120 cm·s −1 , variations in water velocity will not cause CaCO 3 deposition [7]. The faster the water flows, the higher CaCO 3 precipitation is within the threshold value (120 cm·s −1 ) of flow velocity at S PS 2 and S PL .…”
Section: Tufa Deposited On Substrates and Its Rate Of Growthmentioning
confidence: 99%
“…The NO3 − concentrations increased with water flow (from 0.73 mg·L −1 to 1.11 mg·L −1 ), and this may be interpreted as a consequence of nutrient accumulation in the streams. The highest Calcite is the main component of tufa [7], and tufa in Jiuzhaigou is no exception. Three ttufa samples were randomly selected for XRD (two samples) and EDS (one sample) analyses, respectively.…”
Section: Tufa Deposition and Hydrochemistrymentioning
confidence: 99%
See 2 more Smart Citations